A Mild and Simple One‐pot Synthesis of 2‐Substituted Benzimidazole Derivatives Using DDQ as an Efficient Oxidant at Room Temperature. Issue 1 (24th October 2014) - Naeimi, Hossein; Babaei, Zahra
Abstract A series of 2‐substituted benzimidazoles were prepared through one‐pot reaction of o‐phenylenediamine with various aryl aldehydes in the presence of 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone (DDQ) in acetonitrile as solvent at room temperature. The reactions were smoothly preceded in excellent yields and short reaction times with an easy work‐up. The pure benzimidazoles as products were confirmed and characterized by physical and spectral data.